2013
DOI: 10.5901/jesr.2013.v3n4p53
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Community Participation in the Provision of School Plant in the Administration of Public Secondary Schools in Enugu State

Abstract: The study examined the extent of community participation in the provision of school plant in the administration of public secondary schools in Enugu State. One research question and one null hypothesis guided the study. Descriptive survey research design employing simple random sampling was used to sample 7211 of all the principals and classroom teachers from both rural and urban schools in Enugu State: Out of which 702 respondents responded to the study. The instrument used for data collection was questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The study found out that 8 initiatives were required from stakeholders, they include donation of zinc, sand, nails, wood, chairs desks, tables and others. The findings were in agreement with the findings of Okoro in Okenwa & Igbo (2013), who found out that zinc, sand, nails wood, football, basketball valley ball kits, building of assembly, examination and classroom halls are the responsibilities of PTA to provide for schools. The findings of the study were also in conformity with Alu et al (1997), that assembly halls, and classroom blocks are the responsibilities of stakeholders to provide for schools.…”
Section: Discussion Of the Findingssupporting
confidence: 92%
“…The study found out that 8 initiatives were required from stakeholders, they include donation of zinc, sand, nails, wood, chairs desks, tables and others. The findings were in agreement with the findings of Okoro in Okenwa & Igbo (2013), who found out that zinc, sand, nails wood, football, basketball valley ball kits, building of assembly, examination and classroom halls are the responsibilities of PTA to provide for schools. The findings of the study were also in conformity with Alu et al (1997), that assembly halls, and classroom blocks are the responsibilities of stakeholders to provide for schools.…”
Section: Discussion Of the Findingssupporting
confidence: 92%
“…Community support and partnership in facilitating schools in the provision of books, furniture, and funds were also missing. It is confirmed by the studies conducted by Gregoric (2013); Okenwa & Igbo (2013); Epstein (2010); Aguba (2009); Okwor (2008); Cole (2007) that efficient functioning of primary schools without parental and Community Partnership (CP) is not possible. The Well-being, education, and proper development of a child depends on the engagement of the community that is missing in the primary schools of Pakistan.…”
Section: Discussion and Findingsmentioning
confidence: 90%
“…According to Epstein (2010), when SCs are in existence for three years and supported with training, they increase the community involvement in school and thus influence the quality and quantity of family and community connections in the school. The schools are representative of the community and a positive relationship between the both has utmost importance for their development (Cole, 2007;Okenwa & Igbo, 2013;Okwor, 2008). The same type of situation has been identified in some Asian and African countries where policies and program initiatives exist only on paper not on the ground (World Bank, 2006).…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 2 more Smart Citations